Profitability, Growth Opportunity and Capital Structure on Firm Value at Non-Go Public Banks - Desy Nindy Alisa; Dwi Nita Aryani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the effect of profitability, growth opportunity, and capital structure on firm value at non-go public banks. The type of data used in this study is secondary data. From a population of 103 companies, 20 companies were obtained as samples with a period of year 2016-2020 taken by random sampling method. The analytical method of this study uses multiple linear regression analysis with SPSS version 16. The results show that profitability, growth opportunity, and capital structure have a joint effect on firm value. Profitability and capital structure have an effect on firm value, growth opportunity has no effect on firm value. Profitability, growth opportunity, and capital structure simultaneous affect firm value.